Strategi Ekowisata Mangrove Pantai Pohon Cinta Kabupaten Pohuwato Provinsi Gorontalo - Nevi Kurniawati (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
Indonesia is one of the countries with the largest biodiversity and mangrove forests Natural resources, which have not been widely used as tourist attractions, will be under pressure because of the increasing need for life. Developing tourism with the idea of ecotourism is a way best way to utilize local resources. Ecotourism is an operational concept of the concept of sustainable development. Ecotourism is a combination of conservation and tourism. This research aims to examine the potential of the Cinta Tree mangrove area for ecotourism development. This research was carried out using a qualitative descriptive approach. conclusion of this research The strategy for increasing community participation in increasing tourism potential in efforts to develop ecotourism is to increase community understanding about ecotourism, the concept of ecotourism must be introduced and socialized openly, increase community confidence that ecotourism development can improve their economy and this can be achieved by maintaining environmental sustainability, making cooperation agreements for ecotourism development with relevant institutions, actively involving the community in preparing Pohuwato ecotourism development plans, starting from planning, and monitoring and evaluation, will produce positive results for the community, indirectly providing conservation education to society as a whole, not just a particular group of individuals.